The burden of different pathogens in acute diarrhoeal episodes among a cohort of Egyptian children less than five years old - El-Shabrawi, Mortada; Salem, Mohammed; Abou-Zekri, Maha; El-Naghi, Suzan; Hassanin, Fetouh; El-Adly, Tarek; El-Shamy, Ayman (Gastroenterology Review/Przegląd Gastroenterologiczny, 2015)
Introduction: Diarrhoea continues to cause significant morbidity in Egypt. Aim: To determine the frequency and distribution of different enteropathogens in acute diarrhoeal episodes, utilising an expanded testing regimen, and to correlate clinical signs and symptoms associated with the detected pathogens. Material and methods: The case-control study enrolled 356 patients < 5 years old with acute diarrhoea and 356 age and sex-matched healthy controls. Both cases and controls underwent a full history and physical examination, and provided two rectal swab specimens and a stool sample. Laboratory analysis included stool culture, microscopy, and indirect methods. Results : Rotavirus was detected in 11% of patients. Enterotoxigenic Escherichia coli (ETEC), Campylobacter, Shigella, and Salmonella were detected in 7%, 3.7%, 1.1%, and 1.4% of patients, respectively; and in 11.1%, 3.1%, 0.6%, and 0.6% of controls, respectively, with no significant statistical difference. Cryptosporidium was detected in 3.9% of cases. Mixed infection was detected in 5.9% of cases and 0.9% of controls, with a significant difference (p < 0.001). No pathogen was detected in 66.3% of cases and in 83.5% of controls. Rotavirus infection was associated with recurrent vomiting, dehydration, and hospitalisation. Bacterial diarrhoea was associated with vomiting (52%) in ETEC infections, fever (80%) in Salmonella infections, mucus (100%) and blood (50%) in stools of Shigella infections, and convulsions (15%) in Campylobacter infections. Conclusions : Rotavirus is a prominent cause of diarrhoea among Egyptian children. Despite utilising an expanded testing regimen, more work is still needed for identification of other enteropathogens that constitute other causative agents of diarrhoea.